Globe luxation in histiocytosis X. Issue 8 (August 1988) - Wood, C M; Pearson, A D; Craft, A W; Howe, J W
Abstract : A boy with histiocytosis X, first diagnosed at the age of 9 months, presented at the age of 5 years with left globe luxation. Under general anaesthesia the globe was reduced and a temporary paracentral tarsorrhaphy carried out. He was started on a course of oral steroids. Two years later he had normal visual acuity, full ocular movements, and healthy fundi.